Seeing the broader picture: Stakeholder contributions to understanding infrastructure impacts of the Interoceanic Highway in the southwestern Amazon - Perz, Stephen G.; Mendoza, Elsa R.H.; Pimentel, Alan dos Santos [UNESP] (Elsevier, 2022)
There is a large research literature on the impacts of roads and other infrastructure, which highlights the economic benefits, environmental harms and social problems. Most previous research on infrastructure impacts adopts a top-down approach, such as via the use of governmental or remotely-sensed data. This paper argues that a bottom-up approach that features stakeholder perspectives offers complementary advantages to understanding infrastructure impacts that can support improved planning and governance. We conducted stakeholder workshops about impacts of the Interoceanic Highway in the tri-national “MAP” frontier of the southwestern Amazon. The findings confirm previous research in several respects, but also indicate several contrasts. The range of impacts is much broader than topics featured in previous research, and some of the most commonly reported problems, such as diverse forms of crime, have been rarely studied as infrastructure impacts. We conclude by discussing the implications, in terms of criminological research on infrastructure impacts, synergies among diverse impacts of infrastructure, and improved planning of infrastructure for better governance of impacts.
Keywords: Amazon; Development; Environment; Governance; Infrastructure; Stakeholder